Japanese manufacturing foreign direct investment in Singapore. - Chow, Ching Sian. (2008)
Findings from this research show that most Japanese manufacturing companies chose to invest in Singapore because they find Singapore's business environment, investment climate, infrastructure, investment incentives, and high productivity and efficiency attractive. Most of the Japanese manufacturing companies in Singapore are wholly owned subsidiaries. The degree of control over the design and quality, and price of the products manufactured were the main determinants of their choice of operation mode. It was also found that the Japanese parent companies are more likely to use Singapore as a platform to further invest in Singapore's neighbouring countries such as Malaysia and Indonesia. In addition, the two most significant impacts from the recent Asian econommic crisis were the decrease in demand from Asian and local markets.